Abundance and traits link predator ontogeny to prey communities. Issue 6 (21st April 2020) - Start, Denon
Abstract: Function and abundances shape species interactions and thus ecological communities. While communities are often summarized as the mean function of each species, intraspecific variation in traits and thus function is an important driver of community composition. Ontogeny is a common source of intraspecific variation, but while age‐related functional changes can alter species interactions, so too can the effects of those functions on the density of the focal organism. For instance, ontogenetic variation can trigger higher levels of cannibalism, reducing abundances and altering interspecific interactions. I manipulate ontogenetic variation in damselfly larvae to show that intraspecific variation can impact communities through two distinct mechanisms. First, within‐species differences affect population sizes, and thus indirectly shape communities (indirect effect). In particular, ontogenetic variation resulted in smaller damselfly populations, likely because of increased cannibalism rates, and thus ontogenetically diverse populations had a smaller total effect on their prey. Second, trait variation can affect communities by creating differences in the strength of per capita species interactions (direct effect). In this case, damselfly populations with greater age variation had smaller per capita effects on prey communities. I conclude that ontogeny of a single species can directly and indirectly shape community composition.